Alternative splicing and calcium ion channel diversity - Lipscombe, Diane (Henry Stewart Talks, 2011)
Calcium, Cellular Functions, Voltage-gated calcium channels, Functional and structural diversity, Multiple subunits, Multiple genes, Gating, permeation, modulation, Alternative pre-mRNA splicing, cell-specific splicing factors, CaV2.2 N-type channel, Splicing and G protein inhibition